On-line Monitoring of GIS Using Fourier Transform Infrared Spectroscopy. (June 2020) - Zheng, Wenjie; Li, Chengqi; Qin, Jiafeng; Li, Jie
Abstract: Different decomposition component gases caused by different insulation defects in gas-insulated switchgear will accelerate insulation degradation, which is a major threat to human and equipment safety. In this paper, we proposed online monitoring of GIS based on Fourier transform infrared spectroscopy. Firstly, we analysed the absorption characteristics of infrared light in SO2 and moisture. Secondly, we introduce the design principle and signal stabilization method of the laser. Thirdly, we propose the methods for measuring the concentration of SO2 and moisture. Finally, experiments with various concentration of SO2 and moisture are deployed, which proves that the GIS on-line monitoring method for decomposed gas has small measurement error and can be applied in practical applications.